Proses rekrutmen politik calon legislatif lokal di Medan pada Pemilu 2009 :: Studi kasus Partai Keadilan Sejahtera - ADELA, Fernanda Putra ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This research aimed to find out more specifically about the recruitment process of legislative candidates by analyzing the processes and mechanisms conducted by Prosperous Justice Party in the face of legislative elections in 2009 in Medan. PKS is one of the major political parties who have plenty of voters. Previously, PKS also had became a political party winning elections in the city of Medan and is the only Islamic party which had obtained the most seats in parliament elections in the history of the city of Medan in Indonesia. Ability of the PKS become one of the major political parties in the city of Medan certainly have relations with how PKS do the recruitment. It makes interesting PKS made the case for research on recruitment processes of legislative candidates in legislative elections in 2009 the PKS in the city of Medan. This research also measured the level of democratization as well as the PKS in the process of recruiting candidates. The approach used is descriptive qualitative and pks as a case study in this research. Data was collected with the method of documentation, interviews and field observations. Recruitment observed in this study operationalization by using such indicators, quality of candidates, the openness of the recruitment process, community participation, and development base with civil society This study successfully demonstrated that the quality of PKS candidates are good enough when viewed from the level of education that almost all legislative candidates PKS is a graduate degree and some have passed the postgraduate level. PKS has two times following the general election after changing the name, so that from the experience, candidates for legislative members of PKS has experienced enough, considering that there are also some legislative candidate who was also member of the previous legislature. Personally, the popularity of candidates for legislative members of PKS is not so high, but PKS as an institution has a high popularity in the community. PKS candidates recruitment process is closed, causing the PKS tends to be more exclusive. This is because efforts to preserve the Islamic ideology as the party with the good succession planning, so that the selection of candidates is highly selective made PKS as a form of consistency to the ideology of the party, and regarded as a cadre of people capable of carrying the PKS remain as party da’wah in the political life of the state. Therefore, the low transparency in the recruitment process. The network expansion effort with civilian communities, PKS continued to show consistency as party da’wah, because the networks are built by PKS concentrated almost entirely to the study group. Then, to show consistency as a clean party, PKS also conducts social contracts with several civil organizations as well as all legislative candidates in internal party PKS was asked to swear and sign the contents of the political contract between the parties with legislative candidates.